Canine large t-cell intravascular lymphoma – report of two cases - Saulo Romero Felix Gonçalves; Dyeime Ribeiro de Souza; Bruno Henrique Albuquerque Paiva; Francisco de Assis Leite Souza; Andrea Alice da Fonseca Oliveira (Brazilian Journal of Veterinary Pathology, 2025)
Intravascular lymphoma is rare in all species and is characterized by the intravascular proliferation of neoplastic lymphocytes, with the central nervous system being the most affected site. The aim was to report two cases of dogs diagnosed with large T-cell intravascular lymphoma. Both dogs showed neurological signs, including ataxia, seizures, and difficulty walking. Macroscopically, malacia in the brain were noted. Microscopically, there was a predominance of large neoplastic lymphocytes within the vasculature, with CD3 positive and negative to CD20, CD79a, PAX-5 immunohistochemical staining, confirming large T-cell intravascular lymphoma. The complexity of this neoplasm highlights the importance of interdisciplinary collaboration among veterinarians for differential diagnosis of central nervous system diseases.